Social viewpoints of sustainability and communal spatial plans - Kos Grabar, Jože (Journal for Geography, 2011)
The author discusses social viewpoints of sustainability from the viewpoint of contents and the preparation-procedure of communal spatial plans of Slovenian communities. The core of his discussion is devoted to: (1) contentual spatial planning instruments used for maintenance and development of the following values: justice, equality, well-being, social inclusion, public health; (2) carrying out the principles of transparency, collaboration, participation in decision-making and democracy in the preparation-procedures of spatial plans, (3) expert quality and coherence of spatial plans. Based on presented differences between professed principles and real outcomes the author gives some suggestions to moderate or annul the mentioned differences.